ANALISA PENATAAN PARKIR KENDARAAN RODA 4 DAN RODA 2 TERHADAP KAPASITAS RUANG PARKIR PADA RUAS JALAN DIPONEGORO KOTA AMBON - Christo Balriyanan; Anthoneta Maitimu; Edison Hukom (Journal Agregate, 2023)
Parking is a state of immobile vehicles that are temporary. Circulation is the movement of poepole or objects that are neede to k through a site, Diponegoro street Ambon City, whose road length is 700 meters , is filled with parking vichles , 4-wheeled and 2-wheeled. On this street, there are also many shooping  facilities and banks. In fact because as vehicles increase in front of the self-service planet 2000 in the afternoon until late evening the volume of perfomance of the traffic and available parking lots and anticipate the growth of vehcles that are increasing year. What are the characteristics of parking spaces on Diponegoro road sections in Ambon City and is the available parking space capacity on Diponegoro road sections still sufficient to accommodate 2-wheeled and 4-wheeled vehicle